ANALISIS PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KEPUASAN KERJA DAN KINERJA APARAT PEMERINTAH - Kartika Desy Tri Nugraheni, Suharno & Bambang Widarno (Universitas Slamet Riyadi, 2017)
The purpose of this study to know the significance of the effect of budgetparticipation and job satisfaction on the performance of government officials and theeffect of budget participation on the performance of government officials jobsatisfaction as an intervening variable. This study is a survey of government officialsSerengan Village District of Surakarta which amounted to 57 people and all used asa sample with census techniques. Methods of data collection used questionnaires anddocumentation. Data were analyzed used path analysis. The results showed thatbudget participation has positive effect on the performance of government officials.Budget participation has positive effect on job satisfaction of government officials.Job satisfaction has positive effect on the performance of government officials.Participation budgeting positive effect on the performance of government officialsvillages as an intervening variable.Keywords: budget participation, job satisfaction, performance